Contribution of Employee Engagement and Interpersonal Relationship to Improve Employee Performance (International Journal of Management and Sustainability, 2016)
The purpose of this study is to investigate the contribution of employee engagement with mediating variabel rapport to improve employee performance of nurses at Advent Hospital in Indonesia. Using Structural Equation Modeling (SEM), the effect between employee engangement, interpersonal relationship and performance were examined. Data were obtained through a questionnaire. Using proporsionate random cluster sampling, there were 418 respondents answered the questionnaire a. Exploratory factor analysis (EFA) was conducted using principal component analysis and principal axis factoring (PAF) found that among four dimensions of interpersonal relationship, rapport is driven factor of interpersonal relationship. The results indicated that satisfaction negatively affect rapport, commitment has positive relationship toward rapport, advocacy has positive influence toward rapport, satisfaction has negative influence toward employee performance, commitment has positive relationship toward employee performance, advocacy has positive influence toward employee performance.